Sweet corn windbreaker’s effect on microweather changes and increases growth and yield of water spinach (Ipomoea reptans Poir.) on the Samas coastal sandy land - Ulfah, Fajarani; Indradewa, Didik; Respatie, Dyah Weny (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
High wind speed is one of the limiting factors for plant cultivation in coastal sandy land. To mitigate this, sweet corn, an annual plant, can be cultivated as a windbreaker. Water spinach is one of the short-lived plants cultivated by farmers in coastal sandy land. The study aimed to figure out the microweather change, growth, and yield of water spinach protected by sweet corn as windbreaker in various planting locations in Samas coastal sandy land. The research had been conducted in Samas coastal sandy land, Bantul Regency, Yogyakarta Special Region, from October to November 2022. The experiment was arranged in Randomized Complete Block Design non-factorial, containing five treatment levels and four repetitions. The treatment of the planting location of sweet corn as a windbreaker is without sweet corn, sweet corn positioned on the “east”, sweet corn on the “east and west”, sweet corn on the “south”, and sweet corn on the “south and north”. The data were analyzed using analysis of variance (ANOVA), and if the difference was marked, the data analysis was proceeded to Tukey HSD with α = 5%. The results showed that sweet corn windbreaker placed on the “east” was the most effective in decreasing wind speed, thereby modifying the microweather of water spinach plot by lowering air temperature and increasing air humidity and soil moisture content during November on the Samas coastal sandy land. Growth, dry matter accumulation, and water spinach yield increased, although the dry harvest index and fresh harvest index did not show any improvement.